Pengaruh Trend Halal Lifestyle dan Gaya Hidup Terhadap Perilaku Belanja Mahasiswa - Siregar, Rosnani; Aini, Ihdi; Sagita, Noni (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
This study explores the impact of the halal lifestyle trend and lifestyle on the shopping behavior of students at the Faculty of Economics and Islamic Business (FEBI), UIN SYAHADA Padangsidimpuan. The research employs a quantitative approach, utilizing both primary and secondary data sources. Data was collected through the distribution of questionnaires to 96 respondents, and the analysis was carried out using SPSS version 23. The results of the study, as determined through partial (t-test) and simultaneous (F-test) analyses, reveal that the halal lifestyle trend does not significantly affect students' shopping behavior. On the other hand, the lifestyle variable demonstrates a positive and significant influence on students' shopping behavior. The combined effect of both the halal lifestyle trend and lifestyle is found to be positively and significantly correlated with the shopping behavior of FEBI UIN SYAHADA Padangsidimpuan students. In conclusion, the presence of the halal lifestyle trend does not result in an increase in students' expenditures or shopping behavior. However, lifestyle choices significantly impact students' shopping behavior, with higher lifestyle preferences leading to increased shopping activities.